Combination of Multiple Low-Risk Lifestyle Behaviors and Incident Type 2 Diabetes: A Systematic Review and Dose-Response Meta-analysis of Prospective Cohort Studies - Khan, Tauseef A; Field, David; Chen, Victoria; Ahmad, Suleman; Mejia, Sonia Blanco; Kahleová, Hana; Rahelić, Dario; Salas-Salvadó, Jordi; Leiter, Lawrence A; Uusitupa, Matti; Kendall, Cyril W C; Sievenpiper, John L (Diabetes care, 2023)
OBJECTIVE: Combined low-risk lifestyle behaviors (LRLBs) have been associated with a reduction in type 2 diabetes risk. This relationship has not been systematically quantified. RESEARCH DESIGN AND METHODS: A systematic review and meta-analysis was conducted to assess the association of combined LRLBs with type 2 diabetes. Databases were searched up to September 2022. Prospective cohort studies reporting the association between a minimum of three combined LRLBs (including healthy diet) with incident type 2 diabetes were included. Independent reviewers extracted data and assessed study quality. Risk estimates of extreme comparisons were pooled using a random-effects model. Global dose-response meta-analysis (DRM) for maximum adherence was estimated using a one-stage linear mixed model. The certainty of the evidence was assessed using GRADE (Grading of Recommendations, Assessment, Development and Evaluations). RESULTS: Thirty cohort comparisons (n = 1,693,753) involving 75,669 incident type 2 diabetes cases were included. LRLBs, with author-defined ranges, were healthy body weight, healthy diet, regular exercise, smoking abstinence or cessation, and light alcohol consumption. LRLBs were associated with 80% lower risk of type 2 diabetes (relative risk [RR] 0.20; 95% CI 0.17-0.23), comparing the highest with lowest adherence. Global DRM for maximum adherence to all five LRLBs reached 85% protection (RR 0.15; 95% CI 0.12-0.18). The overall certainty of the evidence was graded as high. CONCLUSIONS: There is a very good indication that a combination of LRLBs that includes maintaining a healthy bodyweight, healthy diet, regular exercise, smoking abstinence or cessation, and light alcohol consumption is associated with a lower risk of incident type 2 diabetes.
Keywords: Risk; Humans; cvičení; Life Style; riziko; lidé; prospektivní studie; diabetes mellitus 2. typu; životní styl; Exercise; Diabetes Mellitus, Type 2; Prospective Studies